Effects of dry-land vs. in-water specific strength training on professional male water polo players' performance - de Villarreal, E. S.; Suarez-Arrones, L.; Requena, B.; Haff, G. G.; Ramos-Veliz, R. (The Journal of Strength and Conditioning Research, 2014)
We compared the effects of 6-week dry-land and in-water specific strength training combined with a water polo (WP) program on 7 sport-specific performance parameters. Nineteen professional players were randomly assigned to 2 groups: in-water strength group (WSG) (in-water training only) and dry-land strength group (LSG). The program included 3 weekly strength training sessions and 5 days of WP training per week for 6 weeks during the preseason. Ten-meter T-agility test, 20-m maximal sprint swim, maximal dynamic strength (1 repetition maximum), bench press (BP) and full squat (FS), in-water boost, countermovement jump (CMJ), and WP throwing speed were measured. Significant improvements (p < 0.05) were found in the experimental groups in some variables: CMJ in the LSG and WSG (2.35 cm, 9.07%, effect size [ES] = 0.89; and 2.6 cm, 7.6%, ES = 0.83, respectively), in-water boost increased in the WSG group (4.1 cm; 11.48%; ES = 0.70), and FS and BP increased (p < 0.05) only in the LSG group (12.1 kg; 11.27%; ES = 1.15 and 8.3 kg; 9.55%; ES = 1.30, respectively). There was a decrease of performance in agility test (-0.55 seconds; 5.60%; ES = 0.74). Both dry-land and in-water specific strength training and high-intensity training in these male WP players produced medial to large effects on most WP-specific performance parameters. Therefore, we propose modifications to current training methodology for WP players in preseason to include both the training programs (dry-land and in-water specific strength training and high-intensity training) for athlete preparation in this sport.